The Many Faces of Marrow Necrosis - Mourad, Charbel; Omoumi, Patrick; Vande Berg, Bruno (Seminars in Musculoskeletal Radiology, 2023)
Depending on the age and location within the skeleton, bone marrow can be mostly fatty or hematopoietic, and both types can be affected by marrow necrosis. This review article highlights the magnetic resonance imaging findings of disorders in which marrow necrosis is the dominant feature.Fatty marrow necrosis is detected on T1-weighted images that show an early and specific finding: the reactive interface. Collapse is a frequent complication of epiphyseal necrosis and detected on fat-suppressed fluid-sensitive sequences or using conventional radiographs. Nonfatty marrow necrosis is less frequently diagnosed. It is poorly visible on T1-weighted images, and it is detected on fat-suppressed fluid-sensitive images or by the lack of enhancement after contrast injection.Pathologies historically “misnamed” as osteonecrosis but do not share the same histologic or imaging features of marrow necrosis are also highlighted.
Keywords: bone marrow; osteonecrosis; fatty marrow necrosis; nonfatty marrow necrosis; epiphyseal collapse